Payment of Education Insurance Claims from the Insurer to the Insured - Sri Amanda Dewi (UM Purwokerto Press, 2023)
In everyday life humans do not escape from various kinds of threats and risks of danger. humans cannot know what will happen tomorrow, either in the form of a soul mate, sustenance and death ... Law enforcement is needed to provide rule certainty for parties who violate the rules against the insurer in claiming coverage fees that are not in accordance with the agreed agreement. in law enforcement it is also necessary to have legal protection, especially to protect the rights of the insured who are harmed. The research method in this paper uses a normative juridical approach because the author conducts an inventory of laws and regulations governing insurance problems. The imposition of administrative sanctions in the form of written warnings is carried out at most three (3) times in a row for each violation. The period when imposing administrative sanctions in the form of written warnings for insurance companies is a maximum of 30 (thirty) days from the imposition of the administrative sanctions. Protection of consumers harmed by OJK business actors means evidence of integrated supervision, regulation, and consumer protection of financial services institutions. Insurance companies will be subject to administrative penalties in the form of activity restriction if the insurance company cannot overcome the violation which means the cause of the issuance of the last written warning sanction until using the period that has been influenced.